2018
DOI: 10.1038/s41467-018-06573-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular architecture and regulation of BCL10-MALT1 filaments

Abstract: The CARD11-BCL10-MALT1 (CBM) complex triggers the adaptive immune response in lymphocytes and lymphoma cells. CARD11/CARMA1 acts as a molecular seed inducing BCL10 filaments, but the integration of MALT1 and the assembly of a functional CBM complex has remained elusive. Using cryo-EM we solved the helical structure of the BCL10-MALT1 filament. The structural model of the filament core solved at 4.9 Å resolution identified the interface between the N-terminal MALT1 DD and the BCL10 caspase recruitment domain. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
80
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(82 citation statements)
references
References 63 publications
2
80
0
Order By: Relevance
“…The large molecular complexes formed by the helical assembly of DD superfamily members were difficult to determine by their crystal structure because it is impossible to crystallize a helical structure unless the helical periodicity happens to be an integer. With the development of advanced cryo-electron microscopy (EM) technology, many helical filament structures of the DD superfamily, important for SMOC formation, have been determined 18,19,21,[46][47][48][49][50] . These structural studies revealed that members of the DD superfamily use a common assembly mechanism, detected during the structural study of the RAIDD DD/PIDD DD complex, to form the helical filament structure in SMOCs.…”
Section: Smoc Formation By the Dd Superfamilymentioning
confidence: 99%
“…The large molecular complexes formed by the helical assembly of DD superfamily members were difficult to determine by their crystal structure because it is impossible to crystallize a helical structure unless the helical periodicity happens to be an integer. With the development of advanced cryo-electron microscopy (EM) technology, many helical filament structures of the DD superfamily, important for SMOC formation, have been determined 18,19,21,[46][47][48][49][50] . These structural studies revealed that members of the DD superfamily use a common assembly mechanism, detected during the structural study of the RAIDD DD/PIDD DD complex, to form the helical filament structure in SMOCs.…”
Section: Smoc Formation By the Dd Superfamilymentioning
confidence: 99%
“…42-44 and Figure 2A), and a central catalytic domain that shares homology with the proteolytic active site of the caspase family of serine proteases (43). MALT1 also contains an N-terminal death domain (DD), and recent studies suggest that this domain may interact with BCL10 (44). Interestingly, co-IP mapping studies revealed that GRK2 binds to this MALT1 DD (amino acids 1-139) ( Figure 2A).…”
Section: Introductionmentioning
confidence: 97%
“…In effector T cells, the CBM complex forms the core of a filamentous assembly called the POLKADOTS signalosome, which serves as the cytoplasmic site of the terminal steps of the NF-κB-activation cascade (13,14,(18)(19)(20)(21). Contemporaneously with assembly into microns-long filaments, Bcl10 is also degraded (13,(22)(23)(24)(25)(26), and we have previously shown that proteolysis of Bcl10 occurs within the POLKADOTS signalosome via TCR-dependent selective autophagy (18).…”
Section: Introductionmentioning
confidence: 99%
“…Several key details of this polymerization process are known: recent cell-free cryo-electronmicroscopy studies revealed that Bcl10 polymerizes into filaments with a geometrically confined, helical arrangement with other POLKADOTS components (14,20,21). Although the core of the POLKADOTS filament is composed primarily of Bcl10, polymerization of Bcl10 is nucleated by short oligomers of Carma1and the Carma1-driven nucleation of Bcl10 can act as an amplifier of activation signals from the T cell receptor to NF-κB (14).…”
Section: Introductionmentioning
confidence: 99%